A Comparative Study of Ethics and Communication Patterns in Online and Face-to-face Learning - Rahmadianti, Atika; Panduwinata, Lifa Farida (Universitas Negeri Surabaya, 2023)
The development of communication technology has resulted in a new style of communication. Communication between educators and students is no longer done face-to-face in schools. The role of interpersonal communication between educators and students shifts to Smartphones. This study uses a qualitative method with a descriptive approach by analyzing the data in the form of a brief description and using a triangulation technique to check the validity of the data. In this study, the ethics possessed by students are influenced by their surroundings and themselves. Using social media and communication patterns, students can acquire new language styles. But few students also pay less attention to ethics when talking to teachers. Face-to-face learning is considered very effective compared to online learning.